Effects of calcium and phosphorus on aluminium phytotoxicity in soil-Chinese fir system. Issue 1 (January 2021) - Xu, Xiaoli; He, Si; Yang, Huiqin; Zhang, Jinbiao
Abstract: The potential toxicity of soil active aluminium (Al) on Chinese fir was an urgent problem due to the global soil acidification. The aim of this paper was to study the effects of calcium and phosphorus on Al phytotoxicity in soil-Chinese fir system by using soil culture. One year old seedlings of Chinese fir were used as plant materials. The changes and relationship of pH and active form of Al in rhizosphere soil, leaf Al and physiological indexes in seedlings of Chinese fir were analysed. The results showed that the soil pH of all treatments rose at different degree, while the content of exchangeable Al in soil was decreased under different treatments of calcium and phosphorus as compared with the control. The results also showed that the content of Al and MDA in leave was decreased, while an increase in soluble protein content in leave was observed. It was concluded that the alteration in soil rhizosphere environment may be the main factor improving physiological indexes, consequently alleviating Al phytotoxicity in soil-Chinese fir system.